2003
DOI: 10.1016/s1526-9523(03)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sexual Risk Assessment

Abstract: This article describes the use of a self-administered event history calendar and interviews about sexual partners, sexual activity, and contraception within the broader context of the adolescent's life. Constant comparative analysis was used to analyze the event history calendar interview data. Detailed 5- to 9-year sexual histories were obtained on the event history calendars, including patterns of sexual activity progression and triggers for unintended sexual intercourse. Discussions of protective and risky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…Some researchers have used life history calendar techniques in conjunction with interviews (e.g. Martyn & Martin, 2003;Harris & Parisi, 2007;Nelson, 2010;Scott-Ricks & Harrison, 2011). In these studies, priority was given to the qualitative data with basic descriptive statistics used to demonstrate trends in calendar data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have used life history calendar techniques in conjunction with interviews (e.g. Martyn & Martin, 2003;Harris & Parisi, 2007;Nelson, 2010;Scott-Ricks & Harrison, 2011). In these studies, priority was given to the qualitative data with basic descriptive statistics used to demonstrate trends in calendar data.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, some researchers have started to use calendar based life history review instruments qualitatively (Harris & Parisi, 2007;Martyn & Martin, 2003;Nelson, 2010). The appeal of using calendars in a qualitative context not only lies in their capacity to foster insights (Belli & Callegaro, 2009) but can lead to enhanced researcher -participant interaction and better understanding of the issues under investigation (Harris & Parisi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have argued that the use of a history calendar, as compared to a standard biographical questionnaire, improves the validity and quantity of the data collected (Barbeiro and Spini 2015;Belli 2007;Belli and Callegaro 2009;Glasner and Van der Vaart 2009;Martyn and Martin 2003). The calendar is a flexible tool that allows the development of sequential (in the same column or domain of life) and parallel (by comparing the data in different dimensions of life) retrieval strategies (Belli and Callegaro 2009: 35).…”
Section: Contributions and Further Applicationsmentioning
confidence: 99%
“…Alternatively, it is the interviewee who tells his or her own story, also while answering to a question, while pointing at the relevant event or year on the calendar with a finger.. Third, the calendar may make possible the narration of a difficult life event (parental death, illness or negative critical events) that would otherwise be left aside in the narrative interview. In fact, it is sometimes easier for the interviewee to write a traumatic event on a calendar than to mention it during an open interview (Martyn and Martin 2003). It is also easier for the interviewer to ask a question about a difficult life event when it is already mentioned on the calendar by asking, "Can you tell me more about this event?."…”
Section: Contributions and Further Applicationsmentioning
confidence: 99%
“…A greater involvement with school and extra-curricular activities is related to less sexual risk-taking, including later age at initial sexual experience and the use of contraception (Aspy et al, 2012;Kirby, 2002a). In a study analyzing self-reported sexual histories, adolescent girls who participated in extracurricular activities, volunteer clubs, and sports were less likely to be involved in sexual risk (Martyn & Martin, 2003). School involvement is a protective factor under PBT's behavior system (Jessor et al, 1998a(Jessor et al, , 1998b and is found to be associated with sexual risk behavior and mediated by the effect of family structure, class position, and race on youth sexual risk behavior (Ramirez-Valles et al, 1998).…”
Section: School Involvement Adolescents In the Unitedmentioning
confidence: 99%